2016
DOI: 10.1093/ehjci/jew025
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the imaging assessment of prosthetic heart valves: a report from the European Association of Cardiovascular Imaging endorsed by the Chinese Society of Echocardiography, the Inter-American Society of Echocardiography, and the Brazilian Department of Cardiovascular Imaging

Abstract: Prosthetic heart valve (PHV) dysfunction is rare but potentially life-threatening. Although often challenging, establishing the exact cause of PHV dysfunction is essential to determine the appropriate treatment strategy. In clinical practice, a comprehensive approach that integrates several parameters of valve morphology and function assessed with 2D/3D transthoracic and transoesophageal echocardiography is a key to appropriately detect and quantitate PHV dysfunction. Cinefluoroscopy, multidetector computed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
388
1
78

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 470 publications
(468 citation statements)
references
References 124 publications
1
388
1
78
Order By: Relevance
“…8 VARC-2 defines SVD as (i) valve-related dysfunction (mean aortic gradient > _20 mmHg, effective orifice area < _0.9-1.1 cm 2 , and/or dimensionless valve index <0.35, and/or moderate or severe prosthetic valve regurgitation) or (ii) need for a repeat procedure (TAVI or SAVR). Lancellotti et al 9 suggested incorporating an increase in mean gradient during stress echocardiography or at follow-up (possible obstruction 10-19 mmHg; significant obstruction > _20 mmHg). In a recent surgical series, Bourguignon et al 10 defined SVD using strict echocardiographic criteria independent of symptomatic status, including severe aortic stenosis (mean transvalvular gradient >40 mmHg) and severe aortic regurgitation (effective regurgitant orifice area >0.30 cm 2 , vena contracta >0.6 cm).…”
Section: Existing Definitions Of Structural Valve Deteriorationmentioning
confidence: 99%
See 1 more Smart Citation
“…8 VARC-2 defines SVD as (i) valve-related dysfunction (mean aortic gradient > _20 mmHg, effective orifice area < _0.9-1.1 cm 2 , and/or dimensionless valve index <0.35, and/or moderate or severe prosthetic valve regurgitation) or (ii) need for a repeat procedure (TAVI or SAVR). Lancellotti et al 9 suggested incorporating an increase in mean gradient during stress echocardiography or at follow-up (possible obstruction 10-19 mmHg; significant obstruction > _20 mmHg). In a recent surgical series, Bourguignon et al 10 defined SVD using strict echocardiographic criteria independent of symptomatic status, including severe aortic stenosis (mean transvalvular gradient >40 mmHg) and severe aortic regurgitation (effective regurgitant orifice area >0.30 cm 2 , vena contracta >0.6 cm).…”
Section: Existing Definitions Of Structural Valve Deteriorationmentioning
confidence: 99%
“…Stenosis or regurgitation of the bioprosthetic valve should be reported using validated quantitative or semiquantitative methods. 9 The term deterioration implies changes intrinsic to the valve (including wear, fracture, calcification, leaflet tear, and/or disruption of any component). Transoesophageal imaging can improve visualization of morphological aspects of the valve prosthesis and the additional role of 3D echocardiography in this setting is yet to be defined.…”
Section: Echocardiographymentioning
confidence: 99%
“…Tras el implante transcatéter o quirúrgico de una bioprótesis, debe realizarse un estudio ecocardiográfico que incluya la medición de gradientes transprotésicos en los primeros 30 días para obtener imágenes basales (preferiblemente a los ~30 días para la cirugía), otro estudio 1 año después del implante y, a partir de entonces, un seguimiento anual 168 . Debe considerarse la ETE si las imágenes de ETT son de baja calidad y en todos los casos de sospecha de disfunción protésica o endocarditis 169,170 . La fluoroscopia para válvulas mecánicas…”
Section: Evaluación Basal Y Modalidades De Seguimientounclassified
“…El diagnós-tico debe confirmarse mediante ETT, ETE o fluoroscopia, o TC si está fácilmente disponible 169,170 . El tratamiento de la trombosis valvular de prótesis mecánicas es de alto riesgo, sea cual sea la opción que se siga.…”
Section: Tratamiento De La Trombosis Valvularunclassified
“…Диагноз может быть подтвержден с помощью ЭхоКГ, чреспи-щеводной ЭхоКГ, компьютерной томографии [15]. Хирургическое лечение ассоциируется с высоким Р е д а к ц и о н н а я с т а т ь я риском, поскольку выполняется в экстренных усло-виях и является повторным инвазивным вмешатель-ством.…”
Section: комбинированная антитромботическая терапияunclassified